Higher education for public good Perspectives in the new academic landscape in South Africa - Matsiliza, Noluthando S. (AOSIS, 2022)
This book focuses on the knowledge area of higher education governance, organisational dynamics, leadership and decolonisation. We have observed that governance discourse has been excluded in debates that concern the public good. The construct of public good seeks to support higher education that does not support a capitalist view of profit-making, arguably to respond to societal demands and needs such as developmental efforts through academic functions. Higher Education focuses on interconnected multi-disciplinary constructs, intending to provide services for the public good. The issue of public good is an interesting construct that puts universities on the spot since they are expected to be responsive to environmental changes and stakeholder needs through the functioning of accountable governance structures. These governance structures are compelled to comply with policy demands within external and internal environmental factors. This experience has exposed universities to systematic challenges that are local, regional and global, and which forces them to adapt while serving stakeholders and society. This book will also interrogate the governance of South African public universities in the post-decolonisation era and new demands from stakeholders.